Onset insomnia and insufficient sleep duration are associated with suicide ideation in university students and athletes - Khader, Suhaib (J Affect Disord, 2020)
BACKGROUND: Previous work has shown that poor sleep is a prospective risk factor for suicide in clinical populations and might contribute to risk in the general population. The present study evaluated whether sleep distress, onset insomnia, and insufficient sleep are associated with suicide ideation in university students and athletes participating in the 2011–2014 National College Health Assessment (NCHA; n = 113,185). METHODS: In the NCHA survey, students self-reported the presence or absence of suicide ideation within the past 12 months. SLEEP DISTRESS was assessed with an item indicating that “sleep difficulties” were “particularly traumatic or difficult to handle.” ONSET INSOMNIA was assessed as at least 3 nights per week where survey participants reported an “extremely hard time falling asleep.” INSUFFICIENT SLEEP was operationalized as the number of days per week where the participants felt they did not get “enough sleep to feel rested.” All variables were yes/no except INSUFFICIENT SLEEP, which was categorized as 0–1 (reference), 2–3, 4–5, or 6–7 nights. Binary logistic regression analyses examined suicide ideation as the outcome and sleep variable as a predictor, adjusted for age, sex, year in school, recent depressed mood, and survey year. Associations within student-athletes were likewise assessed. RESULTS: 7.4% of students reported suicide ideation within the past 12 months. In adjusted models, this was significantly associated with SLEEP DISTRESS (OR = 3.01, 95% CI [2.86, 3.16], p<0.0001), ONSET INSOMNIA (OR = 1.95, 95% CI [1.86, 2.04], p<0.0001), as well as INSUFFICIENT SLEEP (4–5 nights, OR = 1.41, 95% CI [1.28, 1.56], p<0.0001; 6–7 nights, OR = 1.92, 95% CI [1.74, 2.13], p<0.0001). Although suicide ideation was less common among athletes, ORs were similar for athletes for all sleep variables of interest. CONCLUSION: Sleep distress, onset insomnia, and insufficient sleep were all strongly related to suicide ideation among university students. These relationships were the same among collegiate athletes, even though this group reported less overall suicide ideation. Our findings suggest that university students may benefit from educational materials linking sleep disruption to maladaptive thinking and suicide ideation.